The Influence of Entrepreneurship, Creativity and Business Location on Business Success - Alkusani alkusani; Rida Ilmafa'ati (INNOVATION RESEARCH JOURNAL, 2021)
Micro, small and medium enterprises (UMKM) is one important part of the economy of a country or region. This important role has encouraged many countries including Indonesia to continue to develop UMKM. Although small in scale the number of workers, assets and turnover, but because of the large enough amount, the role of UMKM is quite important in supporting the economy. The success of UMKM is a factor supporting the improvement of various businesses, both micro, small and medium enterprises, especially in Gresik City. This study aims to determine the effect of entrepreneurial spirit, creativity and business location on the business success. of UKM. The method used in this research is quantitative method, the population of this research is 51 UKM. The analysis techn ique used is multiple linear regression analysis followed by t test with significance level 0,05. The results showed that the entrepreneurial spirit , creativity and business locat ions individually and simultaneous significantly affect the business success.